Evaluation and intervention with a patient with Alzheimer’s disease: Lexical anomia - Sánchez, Andrea Belén; Dumitrache, Cristina Gabriela; Calet, Nuria; de los Santos, Macarena (Revista de Investigación en Logopedia, 2016)
Alzheimer’s disease is the most common type of dementia among older people, causing loss of memory and speech problems. Thus, it negatively impacts patients’ quality of life and impedes them to normally perform daily living activities. In this paper the effect of an intervention program proposed for reducing the lexical anomie in a patient of 79 years diagnosed with Alzheimer’s disease at an early stage is analyzed. The program developed specifically for this study, focuses on the reduction of anomie. A single case design A-B was used. The results show that, in relation to the baseline phase at the end of the program the patient improved his lexical denomination, more specifically the words evocation ability. Moreover, the patient’s response time diminished in the intervention phase with respect to the baseline phase. In order to improve the program, future studies need to increase the number of sessions, refine the design baseline and do a follow-up of the patient’s performance.